VAMOS LANÇAR E PLANTAR O VERDE - Scheid, Rafaela Rossana; Fröhlich, Aléxia Birck; Leite, Fabiane De Andrade (Salão do Conhecimento, 2019)
Projeto de extensão realizado no PETCiências da UFFS - campus Cerro Largo-RS